Carbon dot aggregates as an alternative to gold nanoparticles for the laser-induced opening of microchamber arrays. Issue 44 (31st October 2018) - Sindeeva, Olga A.; Prikhozhdenko, Ekaterina S.; Bratashov, Daniil N.; Vostrikova, Anna M.; Atkin, Vsevolod S.; Ermakov, Aleksey V.; Khlebtsov, Boris N.; Sapelkin, Andrei V.; Goryacheva, Irina Yu.; Sukhorukov, Gleb B.
Abstract : Carbon dot aggregates have been proposed for harvesting light energy, which results in the opening of polymer-based containers with cargo. Abstract : Carbon dots (CDs) are usually used as an alternative to other fluorescent nanoparticles. Apart from fluorescence, CDs also have other important properties for use in composite materials, first of all their ability to absorb light energy and convert it into heat. In our work, for the first time, CDs have been proposed as an alternative to gold nanostructures for harvesting light energy, which results in the opening of polymer-based containers with biologically active compounds. In this paper, we propose a method for the synthesis of polylactic acid microchamber arrays with embedded CDs. A comparative analysis was made of the damage to microchambers functionalized with gold nanorods and with CD aggregates, depending on the wavelength and power of the laser used. The release of fluorescent cargo from the microchamber arrays with CD aggregates under laser exposure was demonstrated.